CONTEXTUAL SYNONYMY OF INFORMATION TECHNOLOGY BLOGS DISCOURSE AS A WAY OF CONCEPT REPRESENTATION - E. K. Kovaleva (Вестник Кемеровского государственного университета, 2014)
The paper aims at contributing to the topic of «Contextual synonymy of Information Technology blogs discourse as a way of concept representation» based on cognitive approach. The author tries to find out the role of contextual synonyms describing the content of a concept in a definite field of knowledge, identify some peculiarities of contextual synonyms meaning and functioning, and observe concept representation in particular discourse. 1500 synonyms of Information Technology blogs discourse were studied. It provides better understanding of cognitive mechanisms, shows the way knowledge interpretation and representation takes place, highlights some virtual discourse peculiarities and contributes to the further development of nomination theory. Continuous sampling approach, component analysis method, definitional method, descriptive method, comparison, contextual analysis techniques were used. The author proves that despite widely recognized role of synonyms in conceptual model of the world representation, the impact of contextual synonyms cannot be overestimated as they are of particular interest for studying. They allow observe the underlying cognitive mechanisms. The difference between contextual synonyms denotations becomes unimportant while describing a concept. Thus, contextual synonyms of Information Technology blogs discourse serve for the most complete concept description and perform some important functions.